2019
DOI: 10.29121/granthaalayah.v7.i2.2019.1016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Root and Tuber Crops Acreage Allocation and Yield Adjustment in Nigeria

Abstract: This paper empirically studied the growth pattern and supply response of root and tuber crops farmers in Nigeria using annual time series data sourced from FAO database. The data spanned from 1961-2014 and covered area, yield and price of yam, cassava and potatoes crops. The data were analyzed using the growth model, instability index, production decomposition analysis model and Engel-Granger two-step model. Findings showed that area was responsible for the paradigm shift in the production of selected root and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Sadiq et al(2017) in their study on supply response of cereal crops in Rajasthan State of India observed negative price coefficients for maize and Bajra. Of recent, Sadiq et al(2019) in their study on the dynamics of root and tuber crops' acreage allocation and yield adjustment in Nigeria observed a negative price coefficient for yam.…”
Section: Short-run and Long-run Elasticitiesmentioning
confidence: 99%
“…Sadiq et al(2017) in their study on supply response of cereal crops in Rajasthan State of India observed negative price coefficients for maize and Bajra. Of recent, Sadiq et al(2019) in their study on the dynamics of root and tuber crops' acreage allocation and yield adjustment in Nigeria observed a negative price coefficient for yam.…”
Section: Short-run and Long-run Elasticitiesmentioning
confidence: 99%